EFEKTIVITAS METODE MULTISENSORI TERHADAP KECAKAPAN MENGINGAT KOSAKATA BAHASA INGGRIS PADA SISWA KELAS I SEKOLAH DASAR (Studi Eksperimental di SD Negeri Tembalang Semarang) - Tutupoly, Jessica Florentina; Siswati, S; Widodo, Prasetyo Budi (Faculty of Psychology, Diponegoro University, 2013)
The English competency is one of the most needed ability that have to be masterd in this globalization era.Thissituation makes the English lesson in Indonesia was taught since Elementary school. The English lesson focusedon the ability to master the vocabulary that could support reading, listening, writing and speaking. The aim of thisreasearch is to know how far that the multisensory method effectiveness to increase the memorizing ability of Englishvocabulary. Subject’s characteristic is the first grade students of elementary school aged 6-7 years old. This research usequasi experimental with non-randomized pretest- posttest control group design and involve 66 subjects that devided into experimental group and control group. The treatment that given in this research use the multisensory method.After the last manipulation, subjects expected to master 30 words. The examination of hypothesis used Paired SampleT-Test and the result of Asymp. Sig is 0,000 (p<0,05). This result acknowledge that multisensory method is effective toincrease the memorizing ability of English vocabulary. Based on this result, the elementary educater should teach theelementary student with the unique method that appropriate to children condition and development, stimulate thememorizing ability considering the developmental factors and use an interesting way of teaching.Keywords: Multisensory method, memorizing ability of English vocabulary, First Grade student of elementary school